Assembling a Universe! O universo compartilhado Marvel dos quadrinhos ao cinema - Ferreira, Antonio Davi Delfino (2019)
The Marvel Cinematic Universe is the integration of different film franchises based on the superheroes of the Marvel Comics publisher. In this narrative reality, superheroes coexist in the same universe, influencing each other's stories and culminating in the formation of the team The Avengers. The shared universe, narrative and creative strategy widely explored in comic books, then gains an audiovisual version that revolutionized the cinema of the 21st century. The present research aims to analyze the recriation of the concept of shared universe of comics in the cinema taking as object of study the films of the first phase of the Marvel Cinematic Universe: Iron Man (2008), The Incredible Hulk (2008), Iron Man 2 (2010), Thor (2011), Captain America: The First Avenger (2011) and The Avengers (2012). For this, we revisit the concept of superhero based on Coogan (2006) to identify how these characters appropriate elements from different sources to establish their characteristics, among them the very notion of shared universe. Following Genette's (1989) transtextuality theory, we then discuss how these dialogues are internalized by giving rise to a narrative genre of its own, though quite elastic, and how it shapes itself in comic books and cinema. We argue that the Marvel Cinematic Universe explores in a high degree the dialogical character of the universe of superheroes with other histories, even with their own comics and films. Thus, in the context of the convergence culture defined by Jenkins (2009), the adaptation of the Marvel Universe to the cinema represents a particular case of creative adaptation between comics and cinematographic languages, based on the discussions proposed by Barbieri (2017), Stam (2006), Hutcheon (2013), Campos (2011) and Jeffries (2017). Finally, we analyze the construction of the Marvel shared universe in the cinema in light of these intertextual and intermedia relations and the recent research on narrative ecosystems.